2006
DOI: 10.1093/condor/108.3.591
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Egg Size and Clutch Size with Elevation in a Wyoming Population of Mountain Bluebirds

Abstract: Few studies have examined how avian life-history traits vary within populations as elevation increases and climate becomes more severe. We compared egg and clutch sizes of Mountain Bluebirds (Sialia currucoides) nesting at two elevations (1500 m and 2500 m above sea level) in the Bighorn Mountains of Wyoming over two years. Eggs laid by females at the high-elevation site were, on average, significantly (6%) smaller in volume than eggs laid by their lower-elevation counterparts. Across elevations, egg size show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…The results of several studies across either populations (Lu 2005, Lu et al 2008, 2009) or species (Krementz and Handford 1984, Badyaev 1997, Badyaev and Ghalambor 2001) lend support to this hypothesis. However, other investigators have found that species breeding at high altitudes tend to lay larger clutches (Stewart et al 1977, Weathers et al 2002, Johnson et al 2006).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The results of several studies across either populations (Lu 2005, Lu et al 2008, 2009) or species (Krementz and Handford 1984, Badyaev 1997, Badyaev and Ghalambor 2001) lend support to this hypothesis. However, other investigators have found that species breeding at high altitudes tend to lay larger clutches (Stewart et al 1977, Weathers et al 2002, Johnson et al 2006).…”
mentioning
confidence: 93%
“…Selection might also favor larger eggs at high altitudes because young from larger eggs may have survival advantages in harsh environments (Williams 1994, Christians 2002). Although some investigators have found that birds at high altitudes do tend to lay larger eggs (Hamman et al 1989, Milinkovich 1993, Lu 2005, Lu et al 2008), others have reported no such trend (Taigen et al 1980, Johnson et al 2006). One factor potentially contributing to these apparently conflicting results concerning the effects of altitude on clutch and egg sizes could be differences among studies in the altitudinal gradients over which data were collected.…”
mentioning
confidence: 99%
“…Among different songbirds, the relationship between elevation and clutch size shows considerable variation, with some reports of larger clutches at high elevations (Carey et al 1982, Camfield 2008), similar clutch sizes in high‐ and low‐elevation habitats (Lu 2007, Bears et al 2009), and smaller clutches at high elevations (Krementz and Handford 1984, Hamann et al 1989, Badyaev 1997, Johnson et al 2006). The mean clutch size for Savannah Sparrows in our study was generally higher than for most low‐elevation populations (Table 3).…”
mentioning
confidence: 99%
“…Indeed, previous work with bluebirds demonstrates that females in better body condition lay larger eggs (Johnson et al . , Robinson et al . ).…”
mentioning
confidence: 99%
“…, Johnson et al . ), experience (Weimerskirch , Thompson & Hale , Sydeman & Emslie ) and nestling rearing abilities (Reid & Boersma , Bolton , Blomqvist et al . , Risch & Rohwer ).…”
mentioning
confidence: 99%